Treatment outcomes of tuberculosis patients and associated factors in Bale Zone, Southeast Ethiopia: a retrospective study - Woldemichael, Bedasa (J Int Med Res, 2021)
OBJECTIVE: This study assessed the outcome of tuberculosis treatment and associated factors in Bale Zone, Southeast Ethiopia in 2017. METHODS: This was 5-year retrospective study of a health registry for tuberculosis patients, which was reviewed from 1 September 2011 to 30 August 2016. Data were analyzed, and descriptive and logistic regression analyses were used to identify the factors that were associated with tuberculosis treatment outcomes. RESULTS: Among the 7205 tuberculosis patients, 6325 (87.8%) had a successful treatment outcome and 880 (12.2%) had an unsuccessful outcome. The age groups ≤14 years (adjusted odds ratio [AOR]=2.21), 15 to 24 years (AOR=1.61), 25 to 34 years (AOR=1.86), or 35 to 44 years (AOR=1.65); being treated at a hospital (AOR=1.63) or health center (AOR=2.52); pulmonary tuberculosis-positive (AOR=0.80); or extrapulmonary tuberculosis patients (AOR= 0.78) were the factors that were significantly associated with tuberculosis treatment outcome. CONCLUSIONS: Public health facilities should pay special attention to the identified variables for tuberculosis prevention and control activities, especially focusing on supporting health workers who work at a health post (lowest level of Ethiopia’s three-tiered healthcare system).